Transition properties of X1Σ+, A1Σ−, B1Δ, C1Π, a3Σ+, b3Δ, c3Π, and d3Σ− states of PO+. (April 2021) - Zhang, Meng; Shi, Deheng
Highlights: C 1 Π – X 1 Σ +, C 1 Π – A 1 Σ – and c 3 Π – a 3 Σ + transitions are strong. Lifetimes are 10 – 100 ns for the C 1 Π state and 10 μs for the c 3 Π state. A 1 Σ – 1 – a 3 Σ + 0–, B 1 Δ2 – b 3 Δ3, b 3 Δ2 – a 3 Σ + 1 and d 3 Σ – 0+ – a 3 Σ + 0– transitions are strong. Lifetimes are 0.1 – 10, 10 and 0.1 – 1 ms for the B 1 Δ2, a 3 Σ + 1 and b 3 Δ2 states, respectively. Lifetimes are 10–100, 10–100, and 100 μs for the A 1 Σ – 0–, d 3 Σ – 0+ and d 3 Σ – 1 states, respectively. Abstract: The potential energy curves of the X 1 Σ +, A 1 Σ –, B 1 Δ, C 1 Π, a 3 Σ +, b 3 Δ, c 3 Π, and d 3 Σ – states of PO + and the transition dipole moments between these states were calculated using the CASSCF method, and then the icMRCI approach. To accurately compute the transition properties, core–valence correlation and scalar relativistic corrections were taken into account. The spin–orbit coupling calculations were used to determine the transition properties of the A 1 Σ –, B 1 Δ, a 3 Σ +, and b 3 Δ states, from which no spontaneous emissions were generated owing to the limitations from the dipole–allowed transition selection rule. The radiative lifetime was approximately 10 – 100 ns for the C 1 Π state and 10 μs for the c 3 Π state. Among these dipole–allowed transitions, the emissions from the C 1 Π – X 1 Σ + system was the strongest and was followed by the C 1 Π – A 1 Σ – and c 3 Π – a 3 Σ + transitions. The radiative lifetime was approximately 10 – 100, 10 – 100, and 100 μs for the A 1 Σ – 0–, d 3 Σ – 0+, and d 3 Σ – 1 states, respectively. Those were of the order of 0.1 – 10, 10, 10 – 100, 1 – 100, and 0.1 – 1 ms for the B 1 Δ2, a 3 Σ + 1, a 3 Σ + 0–, b 3 Δ1, and b 3 Δ2 states, respectively. Among the spontaneous emissions generated from these Ω states, those from the A 1 Σ – 1 – a 3 Σ + 0–, A 1 Σ – 1 – a 3 Σ + 1, B 1 Δ2 – b 3 Δ3, b 3 Δ2 – a 3 Σ + 1, d 3 Σ – 0+ – a 3 Σ + 0–, and d 3 Σ – 1 – a 3 Σ + 1 transitions were relatively strong. The transition properties reported herein are expected to provide useful guidelines for the detection in future experiments. Graphical abstract: The radiative lifetimes are approximately 10 – 100 ns for the C 1 Π state and 10 μs for the c 3 Π state. Among all the dipole–allowed transitions involved in this study, the C 1 Π – X 1 Σ + transition is the strongest and then followed by the C 1 Π – A 1 Σ – and c 3 Π – a 3 Σ + transitions. The radiative lifetimes are approximately 10 – 100 μs for the A 1 Σ – 0– and d 3 Σ – 0+ states and 100 μs for the d 3 Σ – 1 state. The lifetimes are approximately 0.1 – 10, 10, 10 – 100, 1 – 100, and 0.1 – 1 ms for the B 1 Δ2, a 3 Σ + 1, a 3 Σ + 0–, b 3 Δ1, and b 3 Δ2 states, respectively. Among all these spontaneous emissions generated from A 1 Σ –, B 1 Δ, b 3 Δ, and d 3 Σ – states, those from the A 1 Σ – 1 – a 3 Σ + 0–, A 1 Σ – 1 – a 3 Σ + 1, B 1 Δ2 – b 3 Δ3, b 3 Δ2 – a 3 Σ + 1, d 3 Σ – 0+ – a 3 Σ + 0–, and d 3 Σ – 1 – a 3 Σ + 1 transitions are strong. The dipole–allowed d 3 Σ – – c 3 Π transition is weaker than the spin–forbidden d 3 Σ – 0+ – a 3 Σ + 0– transition; the dipole–allowed d 3 Σ – – c 3 Π transition is weaker than the spin–forbidden d 3 Σ – 1 – a 3 Σ + 1 transition. Image, graphical abstract